2018
DOI: 10.1002/chem.201800279
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Assembling of Fmoc‐GC Peptide Nucleic Acid Dimers into Highly Fluorescent Aggregates

Abstract: Self-assembling of molecules by non-covalent interactions is one of the most attracting topics in supramolecular chemistry. The use of short peptides or modified nucleotides as building blocks of the aggregates is particularly intriguing, as these are very easy to synthesize; moreover subtle changes in the chemical structure of such building blocks may drastically affect the properties of the aggregates. The ability of Peptide Nucleic Acids to aggregate is yet very little explored, despite its practical applic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
33
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 44 publications
(41 reference statements)
0
33
1
Order By: Relevance
“…This phenomenon has already been observed for aggregates formed by PNAs andi sa ttributed to the interactions of aggregates with solvents. [9,10] The ca ggregates instead show a4 0nmS tokes shift andn oR EES, which suggest ad ifferent polarity of the aggregates. The shift of the absorption band toward higher wavelengths, the sharpeningo ft he bands observed for the aggregatesr elative to those of monomeric species,a nd the fluorescenceo ft he samples suggest the formation of J-type aggregatesi na ll cases.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This phenomenon has already been observed for aggregates formed by PNAs andi sa ttributed to the interactions of aggregates with solvents. [9,10] The ca ggregates instead show a4 0nmS tokes shift andn oR EES, which suggest ad ifferent polarity of the aggregates. The shift of the absorption band toward higher wavelengths, the sharpeningo ft he bands observed for the aggregatesr elative to those of monomeric species,a nd the fluorescenceo ft he samples suggest the formation of J-type aggregatesi na ll cases.…”
Section: Resultsmentioning
confidence: 99%
“…Aggregates of a and t show Stokes shifts of about 80 nm and an increase in the emission wavelength at increasing excitation wavelength (red edge excitation shift (REES); Figure S1 in the Supporting Information). This phenomenon has already been observed for aggregates formed by PNAs and is attributed to the interactions of aggregates with solvents . The c aggregates instead show a 40 nm Stokes shift and no REES, which suggest a different polarity of the aggregates.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These structures, which exhibit interesting broad fluorescence, could be highly useful for the design of novel materials with unique structural and physical properties. Furthermore, it was demonstrated that modifying these molecules with the aromatic protective group fluorenylmethoxycarbonyl (Fmoc) generates aggregates displaying high quantum yield in the visible region with lifetimes on the nanosecond scale . Moreover, protected guanine‐based PNA monomers were shown to assemble into spheres, which further organize into a periodic layer arrangement to produce photonic crystals …”
mentioning
confidence: 99%